VM and CM Universal Filters Based on Single DVCCTA - Neeta Pandey; Sajal K. Paul (Active and Passive Electronic Components)
A universal voltage-mode filter (VM) and a current-mode filter (CM) based on recently proposed active building block, namely, differential voltage current conveyor transconductance amplifier (DVCCTA) are proposed. Both the circuits use a single DVCCTA, two capacitors, and a single resistor. The filters enjoy low-sensitivity performance and low component spread and exhibit electronic tunability of filter parameters via bias currents of DVCCTA. SPICE simulation using 0.25 μm TSMC CMOS technology parameters is included to show the workability of the proposed circuits.